Medication Adherence Behavior Among Patients with Pulmonary Tuberculosis (TB) in West Sumba - de Fretes, Fiane; Eka Putri, Almacitra Rambu; Elingsetyo Sanubari, Theresia Pratiwi (Poltekkes Kemenkes Jakarta III, 2024)
The recovery of Tb patients depends on medication adherence. Drug side effects, duration of treatment, health control, and social stigma towards Tb patients influence adherence. The assumption that Tb is a hereditary disease, a curse, and challenging to cure makes patients unmotivated to take medicine and reluctant to go to health services because of shame. These factors are at risk of increasing drug resistance rates and hindering the recovery process in Tb patients. The purpose of this study was to describe drug compliance in patients with pulmonary Tb in West Sumba. This study used a descriptive qualitative method with a case study research design and an indepth interview technique. The sample selection was made by purposive sampling with the age 20-45 criteria. Data analysis was done by reducing, presenting, and drawing conclusions. The results showed that drug adherence behavior in TB patients was influenced by treatment routines, barriers during treatment, and emotional, informational, and financial support from the social environment. According to the community, Tb is a curse, contagious and dangerous disease, not a cursed one. Therefore, the results of this study should serve as a basis for health workers and health policymakers in the West Sumba region to design health promotion programs on the importance of social support on treatment adherence of Tb patients so that Tb patients can maintain treatment adherence.